O Papel das Nuvens Rasas no Transporte de Vapor D’água - Martins, Jorge A.; Hallak, Ricardo; Gonçalves, Fábio L. T.; Martins, Leila D.; Freitas, Edmilson D.; Dias, Maria A. F. Silva (Ciência e Natura, 2011)
.